Video mosaic: employing an efficient ORB feature extraction technique with hamming distance matching for enhanced performance - H, Shridhar; Harakannanavar, Sunil S.; Kanabur, Vidyashree; H, Jayalaxmi (Institute of Advanced Engineering and Science, 2025)
Video mosaicing is a computer vision and image processing technique used to create a panoramic or wide-angle view from a sequence of video frames. The goal is to seamlessly combine multiple video frames to form a larger and more comprehensive view of a scene. In recent years, the field of image processing has witnessed a growing interest in video mosaic research owing to its application in surveillance and defense applications. This paper introduces an automatic algorithm for video mosaic creation, addressing the alignment and blending of non-overlapping frames within each input video. The proposed algorithm navigates through several key steps to achieve a seamless and continuous mosaic, particularly tackling issues related to camera motion and content variations across frames. The effect of the good number of matches to be chosen while performing frame stitching is evaluated. The proposed algorithm effectively produces a video mosaic with aligned and blended non-overlapping frames, resulting in a visually continuous mosaic. The output video serves as a testament to the algorithm’s prowess in addressing challenges related to video frame alignment and blending.